2021
DOI: 10.1038/s41598-021-91003-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of elemental sulfur on cadmium bioavailability, microbial community in paddy soil and Cd accumulation in rice plants

Abstract: Cadmium (Cd) is highly toxic to living organisms and the contamination of Cd in paddy soil in China has received much attention. In the present study, by conducting pot experiment, the influence of S fertilizer (S0) on rice growth, iron plaque formation, Cd accumulation in rice plants and bacterial community in rice rhizosphere soil was investigated. The biomass of rice plants was significantly increased by S0 addition (19.5–73.6%). The addition of S0 increased the formation of iron plaque by 24.3–45.8%, meanw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…In the present study, the application of S (30 mg S kg −1 ) in Cd-contaminated (available S of 16.5 mg kg −1 , total Cd of 10.16 mg kg −1 ) soil significantly increased the rice grain biomass although it had no obvious effect on the root, leaf and stem biomass (Table 1), implying that the application of S could improve rice grain biomass under high Cd stress and S-deficient. The current results are consistent with those reported by [9,12]. This is because the application of S in S-deficient soils provided sulfur for rice growth and development.…”
Section: Effects Of S Supply On Rice Grain Biomass Under CD Stresssupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, the application of S (30 mg S kg −1 ) in Cd-contaminated (available S of 16.5 mg kg −1 , total Cd of 10.16 mg kg −1 ) soil significantly increased the rice grain biomass although it had no obvious effect on the root, leaf and stem biomass (Table 1), implying that the application of S could improve rice grain biomass under high Cd stress and S-deficient. The current results are consistent with those reported by [9,12]. This is because the application of S in S-deficient soils provided sulfur for rice growth and development.…”
Section: Effects Of S Supply On Rice Grain Biomass Under CD Stresssupporting
confidence: 93%
“…Previous studies reported that excess S supply (60-300 mg S kg −1 ) in moderately Cd-contaminated soils (3.72 and 5 mg Cd kg −1 ) increased rice biomass [8,13]. Similarly, the application of S in low Cd-contaminated (0.79 and 1.5 mg Cd kg −1 ) and low S-containing soils also increased rice biomass [9,12]. However, the application of S in Cd-contaminated (2.22 mg Cd kg −1 ) but high S-containing (797 mg S kg −1 ) soil reduced rice biomass [8].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations